Experimental Research on Aerated Supercavitation Suppression of Capillary Outlet Throttling Noise - Qianxu Wang; Shouchuan Wang; Huan Zhang; Yuxuan Wang; Junhai Zhou; Panpan Zhao; Jia-Bao Liu (Complexity)
The aim of this work is the reduction of the throttling noise when the capillary is used as a throttling device. Based on the theory of bubble dynamics, two-phase flow, and aerated supercavitation, four different sizes of aerated devices used in refrigerator refrigeration systems are designed. Throttling noise and the temperature and pressure of inlet and outlet of the capillary are measured under stable operation. To compare the noise suppression effects in different groups of experiments, we introduced the cavitation number to analyze, revealed the principle of aerated supercavitation to suppress noise, and combined the results of Fluent simulations to get the relationship between the noise suppression effect and the aerated quality. The experimental results showed that the aerated device can obviously suppress the throttling noise of the capillary outlet, up to 2.63 dB(A), which provides a new way for reducing the capillary throttling noise.